Web-Tana: Inovasi pembelajaran sebagai aksi pengurangan risiko bencana bagi siswa di era digital 4.0 - Robby Hilmi Rachmadian; Tasya Khairunisa; Eva Indra Sofiana; Alfyananda Kurnia Putra (Universitas Negeri Malang, 2021)
Malang Raya area is an area that has quite complex natural disaster potential. Based on the geological geomorphological perspective, Malang Raya is located in a subduction zone which causes the area to have intense seismic activity. Seeing this fact, it is necessary to provide the community with appropriate knowledge of earthquake disaster preparedness and disaster mitigation as an effort to reduce the impact of the risk. However, behind these efforts there are groups that are vulnerable in implementing disaster mitigation, namely the children. This is because children have a limited understanding of disaster risks and hazards, resulting in no preparedness when faced with this. Thus, special policies are needed in the form of learning innovations to increase disaster spatial knowledge and disaster risk reduction from an early age. The research methodology used in this research is research and development. The types of data obtained are qualitative and quantitative data. The data analysis technique used descriptive qualitative analysis and descriptive statistics to be valid. The results of this study are